RANCANG BANGUN CLAMP PEMBUKA DAN PENUTUP MOLD KAPASITAS 1 TON DENGAN BANTUAN SYSTEM HYDRAULIC - Rizal Achmadi, Heroe Poernomo (Techno Bahari, 2020)
In mold manufacturing there are several processes including the assembly process. The assembly process is a process that combines the existing parts of the mold and also disassembles the mold. In the mold assembly process using a tool such as a manual clamp to combine the mold and  hammer to disassemble the mold so it is not efficient. Then a clamp tool is made to open and close the mold with the help of a hydraulic system to save energy and time. The method used by the author to design mold clamp is Finite Element method through the selection of several design concepts, the design is assisted by CAD (Computer Aided Design) software for drawing, fabrication, assembly of component components and testing tools to determine the results of the tool clamp mold. Clamp mold tool is designed with dimensions that adjust the capacity of the clamp mold tool that is 1 ton per process. Based on the results of planning and design that has been done, it produces an opening and closing mold clamp tool with dimensions of hydraulic cylinder Ø40 mm x 200 mm. Then a trial was carried out, resulting in a process of opening and closing mold clamp tool with a capacity of 1 ton with the help of hydraulic cylinders and L plates. mold spills with a thickness of 30 mm and a mold gripping plate with a thickness of 25 mm.